A Case of Endocrine Mucin-Producing Sweat Gland Carcinoma: Is it Still an Under-Recognized Entity? - Khaled A. Murshed; Mohamed Ben-Gashir (Karger Publishers, 2020)
Endocrine mucin-producing sweat gland carcinoma (EMPSGC) is a rare low-grade sweat gland carcinoma characterized by immunoexpression of neuroendocrine markers and mucin production. It occurs most frequently at the head and neck region with strong predilection to the eyelids. Up to 2013, only few cases have been reported. However, in the following years, the number of cases reported has increased significantly, which indicates an upsurge in awareness and increased recognition of this neoplasm. Herein, we describe another case of EMPSGC in a 78-year-old man who presented with a 6-mm skin lesion at the lower eyelid. We discuss the clinical, histopathologic and immunophenotypic features of the tumor with particular emphasis on molecular features and prognosis.